Laminectomy for acute transverse sacral fractures with compression of the cauda equina: A neurosurgical perspective - Devin A. Nikjou; Chani M. Taggart; Salvatore C. Lettieri; Michael R. Collins; Owen T. McCabe; Layne A. Rousseau; Iman Feiz-Erfan (World Neurosurgery: X, 2024)
Introduction: Optimal management of transverse sacral fractures (TSF) remains inconclusive. These injuries may present with neurological deficits including cauda equina syndrome. We present our series of laminectomy for acute TSF with cauda equina compression. Methods: This was a retrospective chart review of all patients that underwent sacral laminectomy for treatment of cauda equina compression in acute TSF at our institution between 2007 through 2023. Results: A total of 9 patients (5 male and 4 female) underwent sacral laminectomy to decompress the cauda equina in the setting of acute high impact trauma. Surgeries were done early within a mean time of 5.9 days. All but one patient had symptomatic cauda equina syndrome. In one instance surgery was applied due to significant canal stenosis present on imaging in a patient with diminished mental status not allowing proper neurological examination. Torn sacral nerve roots were repaired directly when possible. All patients regained their neurological function related to the sacral cauda equina on follow up. The rate of surgical site infection (SSI) was 33%. Conclusion: Acute early sacral laminectomy and nerve root repair as needed was effective in recovering bowel and bladder function in patients after high impact trauma and TSF with cauda equina compression. A high SSI rate may be reduced by delaying surgery past 1 week from trauma, but little data exists at this time for clear recommendations.